Nutrient intake, digestibility and nitrogen balance of West African Dwarf goats fed cassava root sievate and cassava leaf meal mixture in their diets - Peter-Damian Chukwunomso Jiwuba (Agraarteadus, 2020)

(untitled)
Four West African Dwarf (WAD) bucks averaging 7.62 kg and aged 8–10 months ere used to determine the intake, body weight changes, digestibility and nitrogen balance of cassava root sievate-cassava leaf meal mixture based diets. The four experimental diets (T1, T2, T3 and T4) were formulated to contain palm kernel cake, brewers' dried grain, molasses, bone meal, limestone, meal, common salt and 0, 20, 40 and 60% cassava root sievate-cassava leaf meal mixture at the rate of 3:1 respectively. The diets were assigned individually to the four animals in metabolism cages in a 4×4 Latin square design experiment. Feed intake, body weight gain, dry matter intake (DMI), nutrient digestibility and the nitrogen balance status of each animal were measured. Results on proximate composition revealed that the nutrient requirements of the goats were adequate. The DMI for the supplement, total DMI, total DMI (g (kg W0.75)–1), CF intake were highest (P < 0.05) for T4. Average body weight gain (g day–1) and average body weight gain (g (kg W0.75)–1) were best (P < 0.05) for T3 and T4. Crude protein digestibility was best (P < 0.05) for T4. Neutral detergent fibre and acid detergent fibre digestibilities were best for T3 and T4. Nitrogen intake (g day–1), nitrogen balance (g day–1) (g (W kg0.75)–1), nitrogen retention (%), nitrogen absorbed (g day–1) (g (W kg0.75)–1), apparent N digestibility (%) and the efficiency of nitrogen utilization were all best (P < 0.05) for and T4. The diet (T4) containing 60% CRSCLM mixture was recommended among the other diets for feeding goats, as it had better performance concerning nutrient intake, body weight gain, nutrient digestibility and utilization.